Optimising Emotions, Incubating Falsehoods 2022
DOI: 10.1007/978-3-031-13551-4_5
|View full text |Cite
|
Sign up to set email alerts
|

Feeling-Into the Civic Body: Affect, Emotions and Moods

Abstract: This chapter accounts for the energising role of affect, emotions and moods in circulating false information throughout the civic body. It starts by charting the trajectory of the role of feelings in understanding citizen-political communications. Their persuasive importance was recognised millennia ago and have been recognised anew in recent decades with the advent of neuroscience and the understanding that emotions are important for decisions and judgements. The chapter highlights three main mechanisms throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 95 publications
1
2
0
Order By: Relevance
“…This paper has presented results from a survey designed to investigate Australian public attitudes towards government surveillance of public social media data for DNSLE purposes. The survey shows that, as in other studies, demographic characteristics such as age and voting preference are important in understanding support for surveillance practices (see Bakir et al 2015;Davis and Silver 2004;Degli Esposti, Ball, and Dibb 2021;Gurinskaya 2020;Huddy et al 2005;Trüdinger and Steckermeir 2017). This survey adds another dimension: the role of place of birth.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…This paper has presented results from a survey designed to investigate Australian public attitudes towards government surveillance of public social media data for DNSLE purposes. The survey shows that, as in other studies, demographic characteristics such as age and voting preference are important in understanding support for surveillance practices (see Bakir et al 2015;Davis and Silver 2004;Degli Esposti, Ball, and Dibb 2021;Gurinskaya 2020;Huddy et al 2005;Trüdinger and Steckermeir 2017). This survey adds another dimension: the role of place of birth.…”
Section: Discussionsupporting
confidence: 59%
“…Trüdinger and Steckermeier's (2017) study of German attitudes towards surveillance found that acceptance rates varied according to what was being surveilled: the use of biometric data in documents (80%) versus the retention of telecommunications data (31%). Demographic characteristics such as gender (Gurinskaya 2020), age (Bakir et al 2015;Nam 2018), ethnicity (Bakir et al 2015), and education levels and internet usage (Trüdinger and Steckermeier 2017) affect attitudes towards surveillance. Acceptance of surveillance is correlated with participants' perception of benefits and risks (Gurinskaya 2020), particularly risks (Nam 2018), and with an individual's political ideology (Nam 2018).…”
Section: Citizen-state Relations and Sociotechnical Imaginariesmentioning
confidence: 99%
See 1 more Smart Citation